PENGAJUAN MASALAH BERBANTUAN EDMODO SEBAGAI UPAYA MENINGKATKAN KEAKTIFAN SISWA DI ERA PANDEMI COVID-19 - Ririn Diyannita Sasanti (Universitas Negeri Gorontalo, 2020)
The pandemic era changes all components of life, including the teaching and learning process as well. Changes from conventional learning to distance learning. Writing this article aims to determine the increasing student activeness in mathematics Long Distance Learning Process that is being carried out during this Covid pandemic. This research method is descriptive and observational in classroom action research. The sample was students of SMK Negeri 1 Jetis Mojokerto with 32 students. The data were collected by giving the task of submitting problems assisted by Edmodo. Data analysis was carried out in 2 stages. The first is done by looking at the number of student answers uploaded in Edmodo. The second analysis was carried out by looking at the questions made and the resulting answers. The results of the resulting data analysis showed that as many as 22 students uploaded their math problem submission assignments, meaning that the students were active in PJJ. Students can make the second analysis of 48 questions, and the solution can also be determined properly. The results showed that by using the task of posing problems, students could be more active in the distance learning carried out.